2023
DOI: 10.21149/14424
|View full text |Cite
|
Sign up to set email alerts
|

Viabilidad de una escala de experiencias de inseguridad del agua en hogares mexicanos

Abstract: Objetivo. Identificar la viabilidad de la Escala de Experiencias de Inseguridad del Agua en el Hogar (Household Water Insecurity Experiences Scale, HWISE, por sus siglas en inglés) como herramienta para evaluar las experiencias de hogares mexicanos en relación con la inseguridad en el acceso al agua. Material y métodos. La escala fue integrada en la Encuesta Nacional de Salud y Nutrición Continua 2021 (Ensanut Continua 2021) y se utilizaron tres criterios para evaluar su viabilidad: 1) Consistencia interna: Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Mexico has now also included HWISE and a water intermittency scale in nationally representative surveys. The application of HWISE in the National Health and Nutrition Survey (ENSANUT)-2021 demonstrated that HWISE has strong psychometric and predictive validity in the Mexican context ( 49 ), and its application through another nationally representative public opinion poll showed that 32% of Mexican households experienced water insecurity and that 68% of households experiencing severe FI were also experiencing WI (vs. 17% in FS households) ( 50 ). Furthermore, the application of a water intermittency scale in ENSANUT-2022 found that only 31.5% of Mexican households had water 7 days per week, and of these, only 17.4% did not experience water scarcity in the previous 12 months ( 51 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mexico has now also included HWISE and a water intermittency scale in nationally representative surveys. The application of HWISE in the National Health and Nutrition Survey (ENSANUT)-2021 demonstrated that HWISE has strong psychometric and predictive validity in the Mexican context ( 49 ), and its application through another nationally representative public opinion poll showed that 32% of Mexican households experienced water insecurity and that 68% of households experiencing severe FI were also experiencing WI (vs. 17% in FS households) ( 50 ). Furthermore, the application of a water intermittency scale in ENSANUT-2022 found that only 31.5% of Mexican households had water 7 days per week, and of these, only 17.4% did not experience water scarcity in the previous 12 months ( 51 ).…”
Section: Introductionmentioning
confidence: 99%
“…2 ). Nationally representative surveys have been conducted in Mexico [ 16 , 17 ], as well as in Guatemala, Honduras, Peru, and Brazil [ 13 ]; they provide the first estimates of the prevalence of experiences with water insecurity in these countries (Fig. 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…2 ). The inclusion of the HWISE Scale in Mexico’s 2021 and 2022 National Health and Nutrition Survey [ 16 , 18 ] promises to yield a particularly rich set of insights into the role of water insecurity and human health and well-being. Other large studies in LAC that have used the WISE Scales, include an 11-city assessment in Colombia, and a nationally representative survey of 12,745 households carried out by the Brazilian Research Network on Food Sovereignty and Security (Rede Penssan) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%